Pengaruh Citra Bank Terhadap Keputusan Nasabah Dalam Mengambil Pembiayaan Dengan Pelayanan Sebagai Variabel Moderating Pada PT. BPRS al-wasliyah Medan Tahun 2021 - Lubis, Dini Syafitri; Arif, Muhammad; Syahriza, Rahmi (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This research aims to determine (1) The influence of banking image on customer decisions in taking financing at PT. BPRS Al-Wasliyah Medan; (2) The Influence of Banking Image on Customer Decisions in Taking Financing with Services as a Moderating Variable at PT. BPRS Al-Wasliyah Medan. The method used in this research is a quantitative method. The results of the analysis of the influence of the Banking Image variable (X) on the Customer Decision variable in Taking Financing (Y) obtained a value of t = 2.984 (df = 80-3 = 77; t table = 1.99125); (tcount > ttable), with a significant level of 0.001 < 0.05. The results of this research indicate that banking image has a significant positive effect on customers' decisions in taking out financing at BPRS Al-Washliyah Medan by 32.8%. The results of the analysis of the influence of the banking image variable (X) on the customer decision variable in taking financing (Y) which is moderated by service, obtained a value of t = 2.037 (df = 80-3 = 77; t table = 1.99125); (tcount > ttable), with a significant level of 0.005 < 0.05, as a result hypothesis two (H2) is accepted. The results of this research provide an indication that service is able to moderate the influence of banking image on customer decisions in taking financing by 54.9%.